An overview and explication of the extant models of teachers professional development - Ghaith, Ghazi (Beirut, 2013)
This study conceptualizes teacher professional development (TPD) as well as characterizes its effectiveness, following which it provides an overview of the extant modals of TPD that have been used both in Lebanon and internationally. In addition, it explicates with examples, where applicable, the various models as well as provides some comments from a pedagogical perspective on the strengths and limitations of the models under discussion.
: Chapter in a Book
Keywords: Développement professionnel; Professional Development